AB1121 Trabecular bone score combined with clinical risk factors can predict incident fracture in rheumatoid arthritis patients. (15th June 2017) - Kim, D; Cho, S-K; Park, H-R; Choi, YY; Sung, Y-K
Abstract : Background: Fracture is one of the most common and important comorbidities in rheumatoid arthritis (RA) patients, especially patients who use glucocorticoids (GC). However, bone mineral density (BMD) by dual-energy x-ray absorptiometry (DXA) which is the gold standard of diagnosing and monitoring osteoporosis is not a useful tool for predicting new fracture in RA patients. Previous studies suggested the possibility of trabecular bone score (TBS) as a useful predictor for incident fracture. Objectives: We aimed to evaluate the accuracy of TBS combined with clinical risk factors or BMD for prediction of new fracture in patients with RA. Methods: A total of 100 female RA patients were enrolled with assessment of TBS, BMD, and clinical risk factors for fracture. During follow-up period, we calculated the incident rate of all fractures. After dividing the patients according to the use of GCs, we compared baseline characteristics and fracture-free survival between two groups. We compared accuracies of TBS, BMD, clinical risk factors for fracture and their combinations for predicting new fractures using areas under the receiver operator characteristic (ROC) curve (AUC). Results: A total of 14 fractures in 12 patients were occurred among 100 patients during follow-up (428.8 person-years): 9 among the 44 in GC users and 5 in 56 GC non-users. Incidence of fracture was not different between two groups (log-rank test, p=0.27). AUC for incident fracture prediction of TBS alone [AUC 0.54, 95% confidence interval (CI) 0.35–0.72] was comparable with TBS combined with L-spine BMD (AUC 0.54, 95% CI 0.36–0.71) or with hip BMD (AUC 0.55, 95% CI 0.37–0.73). Accuracy for prediction of new fracture is increased when TBS was combined with age and history of previous fracture (AUC 0.74, 95% CI 0.62–0.85). In GC users, history of previous fracture alone (AUC 0.79, 95% CI 0.62–0.97) showed the best accuracy for predicting new fracture among TBS, BMD, clinical risk factors for fracture and their combinations. Conclusions: TBS combined with age and previous history of fracture showed the highest accuracy for predicting new fracture compared to TBS or BMD alone or their combinations in RA patients. In GC users, history of previous fracture alone showed the highest accuracy for predicting new fracture. References: Briot K, Paternotte S, Kolta S, Eastell R, Reid DM, Felsenberg D, et al. Added value of trabecular bone score to bone mineral density for prediction of osteoporotic fractures in postmenopausal women: the OPUS study. Bone 2013;57:232–6. McCloskey EV, Oden A, Harvey NC, Leslie WD, Hans D, Johansson H, et al. A Meta-Analysis of Trabecular Bone Score in Fracture Risk Prediction and Its Relationship to FRAX. J Bone Miner Res 2016;31:940–8. Disclosure of Interest: None declared